Decreased expression of corticotropin-releasing factor-binding protein mRNA in ACTH-secreting pituitary adenomas - Dieterich, K. D.; Lehnert, H. (Experimental and Clinical Endocrinology & Diabetes, 2000)
Summary: This study was designed to analyze the sequence and the expression of CRF-BP mRNA in ACTH-secreting pituitary adenomas. Direct sequencing analysis revealed no apparent mutations in the CRF-BP mRNA. Thus, we conclude that mutations in the coding region of the CRF-BP gene are not involved in the pathogenesis of Cushing's disease. However, using a semiquantitative PCR approach coamplifying the housekeeping gene GAPDH we detected a reduced expression of CRF-BP mRNA in ACTH-secreting pituitary adenomas when compared with normal pituitaries. We suggest that the decreased CRF-BP gene expression in ACTH-secreting pituitary adenomas is most likely an effect due to high cortisol levels in Cushing patients.
Keywords: CRF-BP; mRNA; pituitary adenoma; mutation